PSYCHOLOGICAL FACTOR AND QUALITY DIMENSIONS ON FAST FOOD CONSUMPTION BEHAVIOR - Mardiansyah, Mardiansyah; Nurliza, Nurliza; Dolorosa, Eva (Jurnal Sains Mahasiswa Pertanian, 2018)
Consumption transition of society move out on food pattern which inclined fat contains and high calorie as like fast food. More factor was influence consumer on fast food consumption behavior, that is psychological factor and quality dimensions. The purpose of this research is to analyze the influence of psychological factors (learning, information processing, change of attitude and anxiety) and quality dimensions (price, flavor, packaging, service and brand) on fast food comsumption behaviour on 150 respondent by purposive sampling with descriptive method used analysis Structural Equation Modelling (SEM). The results show that pshycological factors do not affect on consumtion behavior. However, quality dimensions attribute is the primary factor on fast food consumtion behavior than followed by price, flavor, packaging, service and brand. The highest influence in service was consumer loyality. Thus, producer have to create some queue line so that making short time, and arrange room weather which more privacy without have to less room arrangement was avaible.Â